How ex-auditors remember their past: The transformation of audit experience into cultural memory - Daoust, Laurence; Malsch, Bertrand (Accounting, Organizations and Society, 2019)
Researchers have examined the socialization of auditors at various stages of their professional development, but they have done little or no work on the continued effects of this socialization after auditors leave the firms. Put simply, they have not explored the ways that ex-auditors remember their past. Drawing on the literature in social memory studies and on 37 semi-structured interviews with ex-auditors who used to be employed at large Canadian accounting firms, we perform memory work to examine how ex-auditors transform their audit experience into cultural memory. The narratives of past audit experience elicited during the interviews reveal that ex-auditors develop a complex contemporary representation of this experience. When they solicited their communicative (individual) memories, our participants remembered multiple conflicts between their self-identity and the normative work environment during their time at the firms. However, when they reflected on the impact of their audit experience on their new careers, an alternative and much more collective version of this past emerged. Cultural memories with an elitist and class work dynamic that maintained and justified claims of professional and social superiority began to predominate. We argue that communicative and cultural memory are connected because it is communicative memory that allows cultural memory to take on social forms and exercise cultural domination. Our study makes three important contributions. First, it broadens the socio-temporal perspective of auditing research by highlighting the continued effects of the professional identity of auditors after they change careers. Second, it shows that representations of the past provide ex-auditors with a powerful means to promote their professional interests and structure power relationships within organizations. Third, it introduces the use of reflexive memory work as a rigorous methodological approach in accounting and organizational research.